The preparatory colleges 1926-1961 : an experiment in Irish education - Jones, Valerie A. (Trinity College (Dublin, Ireland). School of Education, 2000)
This dissertation examines recruitment to primary teaching through the preparatory system during the period: 1926-1961. The system consisted of seven residential second-level schools, mainly situated in the Gaeltacht, three for boys, three for girls, and one co-educational school for Protestant students. The language of classroom work, extra-curricular activities and all other personal intercourse was Irish; in effect each college was a 'mini-Gaeltacht.' The thesis examines the context in which the preparatory system was established. The restoration of the Irish language was one of the primary aims o f the newly-independent Irish Free State and the education system was seen as having a major role to play in achieving this aim. The thesis analyses efforts to revive the language in the nineteenth century and discusses how it came to assume such importance in the struggle for independence. The work of the Ministry for Irish and the two documents it produced: The Report of the Ministry for Irish to the First Dail, in June 1920, and The Report of the Ministry of the National Language, in August 1921, are studied as are papers from the Departments of the Taoiseach and Finance, and Cabinet documents in the National Archives.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin